1995
DOI: 10.1152/jappl.1995.79.1.279
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum lipids and apolipoproteins after exercise in men with high cholesterol: influence of intensity

Abstract: The purpose of this study was to characterize the short-term changes in blood lipid and apolipoprotein concentrations in healthy hypercholesterolemic men after high-intensity [80% maximal O2 uptake (VO2max); n = 20] or moderate-intensity (50% VO2max; n = 19) cycle ergometer exercise balanced for caloric expenditure (350 kcal). The men's age, height, weight, %fat, and VO2max were 46 +/- 2 yr, 173 +/- 7 cm, 82.7 +/- 2.2 kg, 28 +/- 1%, and 31.1 +/- 1.0 ml O2.kg-1.min-1, respectively. Blood samples were drawn befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
7
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 0 publications
9
65
7
5
Order By: Relevance
“…The augmented insulin sensitivity is apparent immediately after exercise (36) and persists for 20 h to 48 h thereafter (35,37,38). It is also well established that a single bout of aerobic exercise results in 10% to 25% reductions in triglycerides (TGs) and 7% to 15% increases in high-density lipoprotein (HDL) cholesterol levels (11,(41)(42)(43). These lipid changes become apparent between 24 h and 48 h after exercise in both untrained (41,42) and trained subjects (43) in response to caloric expenditures of 350 kcal to 500 kcal and 1000 kcal, respectively.…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 99%
See 1 more Smart Citation
“…The augmented insulin sensitivity is apparent immediately after exercise (36) and persists for 20 h to 48 h thereafter (35,37,38). It is also well established that a single bout of aerobic exercise results in 10% to 25% reductions in triglycerides (TGs) and 7% to 15% increases in high-density lipoprotein (HDL) cholesterol levels (11,(41)(42)(43). These lipid changes become apparent between 24 h and 48 h after exercise in both untrained (41,42) and trained subjects (43) in response to caloric expenditures of 350 kcal to 500 kcal and 1000 kcal, respectively.…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 99%
“…It is also well established that a single bout of aerobic exercise results in 10% to 25% reductions in triglycerides (TGs) and 7% to 15% increases in high-density lipoprotein (HDL) cholesterol levels (11,(41)(42)(43). These lipid changes become apparent between 24 h and 48 h after exercise in both untrained (41,42) and trained subjects (43) in response to caloric expenditures of 350 kcal to 500 kcal and 1000 kcal, respectively. Additionally, the blood pressure-lowering effect of acute aerobic exercise has been long established (44).…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 99%
“…Several studies have reported that after an aerobic exercise TC and LDL-C concentrations were reduced by 3~5% and 4~8% respectively compared to their initial values [3][4][5] . Elevated body temperatures during heat exposure might be the cause of the changes in TC and LDL-C concentrations found in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Physical exercise has been reported to cause 1~6% reduction of TG [3][4][5] . Serum TG concentration might have decreased because energy consumption might have increased due to the increase of metabolic rate caused by heat exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation